INTELLIGENT WEB APPLICATIONS AS FUTURE GENERATION OF WEB APPLICATIONS - Wakil, Karzan; N.A.Jawawi, Dayang (Universitas Negeri Semarang, 2019)
During the recent years World Wide Web very fast increased a fundamental part in our everyday life. In commerce, personal relationship, the effect of the universal network has wholly changed the way people interact with each other and with machines. The problem is after rising the Artificial Intelligence to presenting human feelings, everything changed including web applications. In this paper, we describe the intelligent web applications as present and future of web applications, moreover we highlight the special features and their roles in increasing intelligence of web applications as well as impact this application in the process development web systems. The goals of this paper led to developers to create smart and modern web applications.